An investigation into the perceived importance of service and facility attributes to hotel satisfaction - Shanka, Tekle; Taylor, Ruth (The Haworth Hospitality Press, 2003)
In a complex service environment such as the hotel sector, assessing the perceived importance of services and facility attributes provides management with information not only to benchmark their service level provision, but also to retain and increase their customer base. The present study examines the perceived importance of the service and facilities attributes provided by a 3-star hotel. Results of the self-administered survey of 101 guests of three 3-star hotel properties in Perth (Western Australia) indicated that 13 of the 18 attributes were perceived as important. The 18 services and facility attributes were factor-analysed and three components emerged: physical facilities service experienced and services provision. These three components were found to significantly contribute to the overall importance rating of the hotel attributes. Statistically significant differences were noted for age and residence on the physical facilities and services provided components. Results were discussed and implications with further research opportunities were suggested. © 2003 by The Haworth Press, Inc. All rights reserved.